PTH-074 A case series of patients given successive rescue therapy for steroid refractory severe ulcerative colitis. (June 2019) - Abdulla, Muaad; Prusak, Ewa; Cannon, John Paul; Tighe, Richard; Tremelling, Mark
Abstract : Introduction: Following intravenous steroid use, salvage therapy for acute, severe Ulcerative Colitis consists of infliximab or ciclosporin. Conventional escalation therapy beyond this comprises referral to the surgeons for colectomy and this is our usual practice too. Previous studies where Infliximab or ciclosporin were given as third line therapy have suggested modest efficacy and highlighted potential adverse effects. We sought to review patients under our care who were treated with successive rescue therapy using Infliximab and ciclosporin or vice versa in steroid refractory UC Methods: A retrospective review of case notes was undertaken at the Norfolk and Norwich University Hospital. Between February 2017 and June 2018 eight patients with steroid-refractory ulcerative colitis given ciclosporin and infliximab therapy in succession were identified. The success and safety of treatment was assessed alongside the biochemical changes during treatment. 12 month follow up was reviewed post treatment. Results: Ages ranged from 17 to 41. One patient was known to have pancolitis, while seven had at least distal/left sided colitis. Six patients were switched from ciclosporin to infliximab (Cic-Ifx) and two patients were switched from infliximab to ciclosporin (Ifx-Cic). Reasons for switching included intolerance to treatment and concerns about fertility with future ileal pouch formation. Five out of eight patients responded to treatment and avoided surgical intervention during admission. The remaining three patients were referred for colectomy which they underwent without complications or a prolonged post-op stay. All five patients undergoing successive rescue therapy avoided colectomy up to 12 months post treatment. There were no deaths, or significant adverse events reported in all eight patients. Three patients were given intravenous antibiotics due to suspected bacterial translocation. Conclusions: In this small case series colectomy avoidance was 62.5% in patients who were given alternative rescue treatment during admission and remained medically managed for at least 12 months following the intervention. In contrast to other studies there were no significant adverse outcomes encountered. Careful monitoring and selection of patient profile may help determine who benefits most from successive salvage therapies in acute, severe UC.